2005
DOI: 10.1088/0031-9155/50/4/r01
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in diffuse optical imaging

Abstract: We review the current state-of-the-art of diffuse optical imaging, which is an emerging technique for functional imaging of biological tissue. It involves generating images using measurements of visible or near-infrared light scattered across large (greater than several centimetres) thicknesses of tissue. We discuss recent advances in experimental methods and instrumentation, and examine new theoretical techniques applied to modelling and image reconstruction. We review recent work on in vivo applications incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
863
1
10

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,052 publications
(878 citation statements)
references
References 254 publications
(334 reference statements)
4
863
1
10
Order By: Relevance
“…During forepaw stimulation the electrodes near the primary somatosensory cortex (SI) resolve the characteristic SEP components, which correspond to SI activation. DOI has been used to measure hemodynamic evoked responses in several cortical areas in both humans and animals (Boas et al, 2004;Durduran et al, 2004;Gibson et al, 2005;Hillman et al, 2007;Hoshi, 2003;Obrig and Villringer, 1997;Villringer and Chance, 1997). Previously, we have shown that in rats we are able to detect evoked hemodynamic responses both spatially and temporally equivalent to fMRI (Culver et al, 2005;Culver et al, 2003;Siegel et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…During forepaw stimulation the electrodes near the primary somatosensory cortex (SI) resolve the characteristic SEP components, which correspond to SI activation. DOI has been used to measure hemodynamic evoked responses in several cortical areas in both humans and animals (Boas et al, 2004;Durduran et al, 2004;Gibson et al, 2005;Hillman et al, 2007;Hoshi, 2003;Obrig and Villringer, 1997;Villringer and Chance, 1997). Previously, we have shown that in rats we are able to detect evoked hemodynamic responses both spatially and temporally equivalent to fMRI (Culver et al, 2005;Culver et al, 2003;Siegel et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Optical tomography of the entire brain is also limited to newborn infants, since the attenuation of light across a larger head is too great to sample the inner regions of the brain. Because of the high attenuation, data acquisition is relatively slow, and imaging of evoked response requires averaging over several activations (Gibson et al, 2005).…”
Section: Functional Nirsmentioning
confidence: 99%
“…Optical imaging can provide spectroscopic information on tissue composition [20,21]. Devices for optical imaging are relatively inexpensive, and handheld probebased optical imaging systems have been developed.…”
Section: Biophotonicsmentioning
confidence: 99%